Environmental and socio-economic resources at the landscape level – Potentials for sustainable land use in the Georgian Greater Caucasus. (15th February 2019) - Theissen, Tim; Aurbacher, Joachim; Bedoshvili, David; Felix-Henningsen, Peter; Hanauer, Thomas; Hüller, Sarah; Kalandadze, Besik; Leonhäuser, Ingrid-Ute; Magiera, Anja; Otte, Annette; Shavgulidze, Rati; Tedoradze, Giorgi; et al.
Abstract: Mountain regions cover one quarter of the Earth's terrestrial surface, and are both valuable and vulnerable areas with complex human-environmental interrelationships. In this coupled system, land-use changes induced by political or socio-economic transformations generate consequences for ecological landscape functions like soil productivity and species richness, and integrative land-use concepts provide the potential of a sustainable land development. In the Kazbegi region in the central Greater Caucasus of Georgia, these transformations further lead to landscape-structure change and population marginalization. Hence, we developed three agricultural land-use scenarios that meet Agenda 2030 Sustainable Development Goals to ensure a sustainable rural land development and the conservation of mountain ecosystems. Our normative scenario approach integrates quantitative and qualitative findings of empirical research in landscape ecology, soil science, vegetation ecology as well as agronomics and socio-economics. According to the examined environmental and socio-economic resources, we defined various scenario logics and normative assumptions that combine optimized livestock production (in dairy cow keeping and cattle fattening) with ecological limitations to maintain the functioning of mountain ecosystems. The rule-based scenarios achieved measurably increased outputs in biomass yields, livestock production and related revenues at the regional scale. Further, GIS generated scenario maps demonstrate the related land-use patterns spatially explicit and in high resolution, and visualize the alternative future from local to the regional scale. In conclusion, scenario development helps to determine region-specific and integrated land-use options to provide a sound base for land users and decision makers. Based on research on multiple landscape functions, this approach can assist sustainable land development in a mountain region. Graphical abstract: Image 1 Highlights: We developed normative scenarios based on qualitative and quantitative research. Our study covers landscape and vegetation ecology, soil science and socio-economics. Cattle fattening and dairy cow farming meet the local demand for milk and meat. Even with strong protection measures a surplus is achieved. Land-use scenarios can uncover untapped potentials.